Getting involved with The Job among nurses and its effect on Organizational Citizenship Behavior: the Mediating Role of Job Satisfaction - A Fathiizadeh; R Zare; A Bahmani (Iran University of Medical Sciences, 2018)
Abstract Background & Aim: Organizational citizenship behavior has an important role in providing effective products and services for internal and external customers of the organization and by improving effective use of resources it may lead to the improvement of functions and the increase in productivity. The objective of this research is to study the impact of job involvement on the organizational citizenship behavior by exploring the mediating role of job satisfaction. Materials & Methods: The study is a cross-sectional and descriptive-correlational study, and uses a structural equation model by Smart-PLS-7 software. To collect the data, three standardized questionnaires with a five-point Likert scale were used. The Statistical sample included 195 nurses employed in Sirjan hospitals in 2016, selected by the stratified random sampling approach using Cochran's sampling formula. Result: The results showed that there was a positive and significant relationship between job involvement and organizational citizenship behavior among the nurses at the error level of 0.01 and r=0.44. Furthermore, the results indicated a mediating effect of job satisfaction on the relationship between job involvement and organizational citizenship behavior. Moreover, a relationship between job satisfaction and citizenship behavior was found at the error level of 0.05 and r=0.19 in the study population. Conclusion: Nurses' job involvement leads to their job satisfaction and the increase in their self-esteem and the emergence of organizational citizenship behaviors. The nurses' concerns about achieving their goals and organizational values and their involvement in job lead them to enjoy their job and show more empathy.